Automation risks versus skill requirements : occupational determinants of expectations and political preferences in knowledge societies - Andersson, Anton B. [Verfasser]; Lindh, Arvid [Verfasser]; Westerman, Johan [Verfasser] (My University, 2026)
“Over the past half-century, structural developments in production systems and labour markets have brought about substantial shifts in the occupational structure. Individuals’ positions within these societal transformations are widely understood to shape their expectations of the future and their political preferences. While the focus in much recent research in this regard has been on occupations’ susceptibility to automation, this study places the level of skill requirements at the centre of the analysis. Using data from the European Social Survey, we find robust support for this perspective. Individuals in occupations with higher skill requirements tend to anticipate fewer personal economic difficulties and hold more positive views about the direction of societal development, while also being less supportive of government redistribution and less inclined to vote for the radical right. In contrast, the theoretically expected relationships between automation-risk measures and these outcomes generally disappear once skill-level requirements are controlled for. Our theoretical arguments and empirical findings suggest that the role of automation risk may be overstated in understanding how occupational positions shape social and political outcomes, and that the level of skill requirements carries greater explanatory weight in shaping individuals’ expectations about the future and their political preferences in knowledge societies.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; 370; 300; Automatisierung; Arbeitsmarktrisiko; Substitution; Substitutionseffekte; Routinetätigkeit; Qualifikationsanforderung; Qualifikationsniveau; Politische Einstellung; Wissensgesellschaft